2008
DOI: 10.1016/j.expneurol.2008.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Altered neuronal activity relationships between the pedunculopontine nucleus and motor cortex in a rodent model of Parkinson's disease

Abstract: The pedunculopontine nucleus (PPN) is a new deep brain stimulation (DBS) target for Parkinson's disease (PD), but little is known about PPN firing pattern alterations in PD. The anesthetized rat is a useful model for investigating the effects of dopamine loss on the transmission of oscillatory cortical activity through basal ganglia structures. After dopamine loss, synchronous oscillatory activity emerges in the subthalamic nucleus and substantia nigra pars reticulata in phase with cortical slow oscillations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 108 publications
2
23
0
Order By: Relevance
“…Supporting this view are the current observations showing that over a range of frequencies and in two behavioral states, increases in oscillatory activity in the SNpr of the hemiparkinsonian rat are consistently accompanied by increases in coherence between motor cortex and SNpr LFPs. These observations are consistent with evidence that dopamine cell loss facilitates striatal transmission of corticostriatal input to downstream sites (Tseng et al, 2001;Murer et al, 2002;Mallet et al, 2006;Walters et al, 2007;Aravamuthan et al, 2008). Other results of this study, however, suggest that additional processes may be involved in determining the profile of activity in basal ganglia output after dopamine cell lesion.…”
Section: Discussionsupporting
confidence: 90%
“…Supporting this view are the current observations showing that over a range of frequencies and in two behavioral states, increases in oscillatory activity in the SNpr of the hemiparkinsonian rat are consistently accompanied by increases in coherence between motor cortex and SNpr LFPs. These observations are consistent with evidence that dopamine cell loss facilitates striatal transmission of corticostriatal input to downstream sites (Tseng et al, 2001;Murer et al, 2002;Mallet et al, 2006;Walters et al, 2007;Aravamuthan et al, 2008). Other results of this study, however, suggest that additional processes may be involved in determining the profile of activity in basal ganglia output after dopamine cell lesion.…”
Section: Discussionsupporting
confidence: 90%
“…In Parkinson’s disease, the PPN is thought to be underactive due to overwhelming inhibitory input from GPi (Aravamuthan et al 2007, Gomez-Gallego 2007, Zhang et al 2012) and due to neurodegeneration (Jellinger 1988). However, PPN-DBS clinical trials have found inconsistent therapeutic effects in Parkinson’s disease patients (Androulidakis et al 2008, Aravamuthan et al 2008, Jenkinson 2005, Mazzone et al 2005, Plaha and Gill 2005). …”
Section: Discussionmentioning
confidence: 99%
“…However, RTn receives dopaminergic input from A8-A10 mesencephalic groups (Freeman et al, 2001), indicating that dopamine loss might directly affect activity in this nucleus. While dopamine cell lesion alters the phase relationship between pedunculopontine (PPN) nucleus and cortex (Aravamuthan et al, 2008), the phase relationship associated with dopaminergic lesion is not consistent with PPN driving activity in the PFN.…”
Section: Discussionmentioning
confidence: 99%